Reflection on my Schooling: From Engineering to Training (Journal of Training and Development, 2015)
This paper reflects the journey of my life and highlights the importance of setting goals for desired achievements in life. Additionally, it scrutinizes the role of patronage of parents, societal influence and cultural capital to set the degree of success a person achieves in his or her life. Through reflection, the paper advocates for inevitability of technical and vocational contents and multi-disciplinary competencies including international languages and life skills from the early age of schooling to tackle with the challenges of 21st century.DOI: http://dx.doi.org/10.3126/jtd.v1i0.13090 Journal of Training and Development Vol.1 2015: 46-53